2017
DOI: 10.4236/jwarp.2017.92008
|View full text |Cite
|
Sign up to set email alerts
|

Water Resource, Hygienic Practice, and Soil Transmitted Helminthiasis in Some Rural Communities of Osun State, Nigeria

Abstract: Provision of water, sanitation and hygiene (WASH) resources has been advocated as necessary add-on strategy for sustainable control of soil-transmitted helminthiasis (STH) alongside annual mass drug administration (MDA) of albendazole to endemic communities. This study investigated the burden of STH and status of WASH resources in eight rural communities in Aiyedaade LGA, Osun State, Nigeria. Four of the communities were supported with improved water and hygiene resources (Category A), and another four support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
4
2
0
Order By: Relevance
“…those reported by Mogaji et al [2]; Oluwole et al [12] and Fafunwa et al [23] where prevalence estimate within the range 7.1-26.2% was observed. Nevertheless, the prevalence is higher than the 4.13% reported by Sam-wobo et al [16].…”
Section: Plos Onesupporting
confidence: 55%
“…those reported by Mogaji et al [2]; Oluwole et al [12] and Fafunwa et al [23] where prevalence estimate within the range 7.1-26.2% was observed. Nevertheless, the prevalence is higher than the 4.13% reported by Sam-wobo et al [16].…”
Section: Plos Onesupporting
confidence: 55%
“…This observation is in line with already established fact that prevalence and intensities of hookworm infections are restricted to adult populations [23]. However, the prevalence recorded in this study (4.6%) is lower than those reported by Mogaji et al [2]; Oluwole et al [12] and Fafunwa et al [21] where prevalence estimate within the range 7.1 -26.2% was observed. Nevertheless, the prevalence is higher than the 4.13% reported by Sam-wobo et al [16].…”
Section: Discussionsupporting
confidence: 92%
“…This finding agrees with a Tanzanian study that found statistically non-significant association between age and latrine adoption (Sara and Graham, 2014). By contrast, a Nigerian study reported significant difference (p = 0.002) in age distribution in terms of adherence to hygiene and sanitation practices (Fafunwa et al 2017). Moreover, mothers or caregivers whose child was 202 48-59 months of age (AOR=2.21, 95% CI: 1.82-2.68) were more likely to practice sanitary disposal of child feces than mothers or caregivers whose child was less than 12 months old (Azage and Haile, 2015).…”
Section: Agesupporting
confidence: 89%